Guidelines for sensory product development and quality control - Carpenter, Roland; Lyon, David; Hasdell, Terry A. (Maryland (Estados Unidos) : Aspen, 2000)
What is sensory analysis used for?
Relationship of physiology and psychology to sensoty analysis.
How to use sensory analysis to meet your objective.
Products for sensory analysis.
Who are the right people for sensory analysis?
Experimental design in data analysis.
Reporting and recording.
Putting sensory analysis into practice.
Product "tasting" is carried out in every food company. It may be morning testing session by the managing director, comparisons or competitor prodcuts by the marketing staff; quality assurance tasting bu a product "expert"; evaluation of new recipes from the product development kitchen; or on-line checking during production. Most relevant, though, is that the people responsible for the tasting session should know why the work is being done and fully reralize if it is not done well, the results and conclusions drawn and their implications are likely to be misleading. If theses Guidelines help to persuade those who organize and participate in food tasting in companies to review and reassess what they are doing, and why, we believe our efforts will have been worthwhile.
Keywords: TECNOLOGIA ALIMENTARIA; INDUSTRIA ALIMENTARIA; ALIMENTOS; QUIMICA ANALITICA; ANALISIS QUIMICO; ITA